Regulating directional transfer of electrons on polymeric g-C₃N₅ for highly efficient photocatalytic H₂O₂ production - Che, Huinan (2022)
Graphite carbon nitride (g-C3N5) has been widely used in various photocatalytic reactions due to its higher thermodynamic stability and better electronic properties compared to g-C3N4. However, it is still challenging to endow g-C3N5 with high performance on photocatalytic hydrogen peroxide (H2O2) production. Herein, potassium and iodine are co-doped into g-C3N5 (g-C3N5-K, I) for photocatalytic production of H2O2 with high efficiency. As expected, the photocatalytic H2O2 production rate over the g-C3N5-K, I (2933.4 μM h-1) reaches to 84.22 times as that of g-C3N5. The excellent photocatalytic H2O2 production activity is mainly ascribed to the co-doping of K and I, which significantly improves the capacity of oxygen (O2) adsorption, selectivity of two-electrons oxygen reduction reaction (2e- ORR) and separation efficiency of charge carriers. The density functional theory (DFT) calculations reveal that O2 molecules are more conducive to being adsorbed on g-C3N5-K, I. Besides, the result of excited states further indicates that photo-generated electrons can be directionally driven to the adsorbed O2 molecules, which are effectively activated to form H2O2. The findings will contribute to new insights in designing and synthesizing g-C3N5 based photocatalysts for the H2O2 production.